Selection for increased in vitro digestibility improves feeding value of sorghum grain - B J Healy; P J Bramel-Cox; B T Richert; C F Klopfenstein; Merle D Witt; Joe D Hancock (Kansas Agricultural Experiment Station Research Reports, 1991)
Six cannulated barrows and two hundred eighty-eight chicks were used in an experiment to determine the value of an in vitro protein digestibility assay (pepsin digest) for identification of sorghum parent lines with improved nutritional value. The barrows were used to determine digestibility of the experimental sorghums at the terminal ileum and for the total digestive tract. Due to a limited supply of the sorghums, broiler chicks were used as a model to predict the value of the experimental sorghums for growth performance. Four sorghum parent lines were selected from 100 SI families grown at several locations in Kansas. Two of the sorghums were consistently low and two were consistently high for in vitro digestibility. Treatments were: 1) corn-soybean meal control; 2) and 3) low digestibility sorghums (LDI and LD2); 4) and 5) high digestibility sorghums (HDI and HD2); and 6) pearl millet (PM). The sorghums that had consistently high in vitro digestibility were of greater nutritional value to pigs and growing chicks than sorghums with low in vitro digestibility. In the pig experiment, digestibility of N at the terminal ileum ranged from 69.6% for LDI to 79.0% for HDl, compared to 81.6% for the corn-based control. Similar responses were noted for digestibility of gross energy, with values of 71.8% and 77.0% for LDI and HDl, compared to 80.2% for the corn-based control. The HD lines were equal or nearly equal to corn in the chick growth assay, with efficiencies of gain that were 98 and 100% that of corn for HD1 and HD2, respectively. Pearl millet was of greater feeding value than sorghums for chicks but less digestible than sorghums in pigs. These data suggest that in vitro pepsin digestibility can be a valuable tool for sorghum breeders to select parent lines with improved feeding value.; Swine Day, Manhattan, KS, November 21, 1991
Keywords: Swine day; 1991; Kansas Agricultural Experiment Station contribution; no. 92-193-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 641; Swine; Performance; GF; Ileal; Digestibility; Sorghum; Millet; Corn